2018
DOI: 10.3386/w24732
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Earnings Gap in the Gig Economy: Evidence from over a Million Rideshare Drivers

Abstract: , and Yale for valuable input. The views expressed herein are those of the author and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w24732.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 37 publications
(3 reference statements)
4
96
2
3
Order By: Relevance
“…We test a number of plausible mechanisms that help explain the sorting of individuals into these types of alternative business opportunities. Our findings therefore contribute to recent work by Katz & Krueger (2017) who investigate the influence of unemployment in the rise of alternative work, Cook et al (2018), who consider the role of gender and particularly the gender earnings gap using data from Uber, and Chen et al (2017) who, also using data from Uber, document the positive wage and earnings effect of flexible work. Relatedly, Burtch et al (2018) analyze how online intermediaries influence local entrepreneurial activity by showing that entrepreneurship (measured with survey data and Kickstarter campaigns) decreases in local areas after the introduction of Uber.…”
supporting
confidence: 50%
“…We test a number of plausible mechanisms that help explain the sorting of individuals into these types of alternative business opportunities. Our findings therefore contribute to recent work by Katz & Krueger (2017) who investigate the influence of unemployment in the rise of alternative work, Cook et al (2018), who consider the role of gender and particularly the gender earnings gap using data from Uber, and Chen et al (2017) who, also using data from Uber, document the positive wage and earnings effect of flexible work. Relatedly, Burtch et al (2018) analyze how online intermediaries influence local entrepreneurial activity by showing that entrepreneurship (measured with survey data and Kickstarter campaigns) decreases in local areas after the introduction of Uber.…”
supporting
confidence: 50%
“…It is also worth considering the possibility that certain factors contributing to the pay gap are not discriminatory. Consistent with gender differences observed in both the psychological literature (e.g., Trivers, ; Buss, ; Shackelford et al, ; Oaxaca & Ransom ; Wang et al, ) and pay gap analyses that have been able to include observed differences consistent with gender differences in psychological attributes (e.g., Bolotnyy & Emanuel, ; Cook et al, ), it may be possible that men and women are, on average, different in ways which are not problematic from a discrimination perspective. However, at the same time, just because there may be biological or evolutionary explanations for group differences do not suggest that the continued existence of such differences is ideal.…”
Section: Discussionmentioning
confidence: 72%
“…If men and women, on average, possess different characteristics, abilities, or interests that are compensated differently in the labor market, then such differences could manifest in group-level differences in pay. For instance, if males and females differ on various psychological dimensions (whether due to upbringing, culture, genetics, biology or some other ultimate cause), certain pay differences may manifest which are truly the result of different individual preferences and life choices, similar to those observed in Bolotnyy and Emanuel (2018) and Cook et al (2018). Such differences may be seen as a non-problematic form of pay gap so long as these differences truly are not the result of discrimination of any kind.…”
Section: Theoretical Perspectives and Hypothesesmentioning
confidence: 87%
“…185 Less controversially, rating and review systems are pointed to (eg, by the European Commission) as an important safeguard for sharing or collaborative economy platforms, especially in the absence of the relevant information or, in some circumstances, the inapplicability of consumer protection rules. 186 The extent to which the reliance upon rating and reputation may have a disparate impact on some groups and constitute a form of (albeit possibly unintended) discrimination, 187 and how 'neutral' systems, even where there is no evidence of consumer discrimination, can still produce unequal outcomes on vectors such as gender pay, 188 has been highlighted. Although the specific area of credit benefits from explicit prohibitions on the use of certain data, even this area sees the use of alternative data sources that may aid in discrimination in practice.…”
Section: The Complexities Of Regulating Ratingsmentioning
confidence: 99%